Green dots, pink hearts : displacing politics from the Malaysian rain forest. - Brosius, J. Peter (American Antropological Association, 1999)
Recent years have witnessed the progressive envelopment of environmental politics within institutions for local, national, and global environmental governance. Such institutions inscribe particular forms of discourse, simultaneously creating certain possibilities and precluding others, privileging certain actors and marginalizing others. Apparently designed to ameliorate environmental destruction, these institutions may in fact obstruct meaningful change through endless negotiation, legalistic evasion, and compromise among Òstakeholders.Ó More importantly, however, they insinuate and naturalize a discourse that excludes moral or political imperatives in favor of indifferent bureaucratic and technoscientific forms of institutionally created and validated intervention. Drawing on Rappaport's insights about Òthe subordination of the fundamental to the contingent and instrumentalÓ (in ÒThe Anthropology of TroubleÓ), I examine this process of institutional development with reference to an international rain forest campaign that focused on Sarawak, East Malaysia, from the late-1980s to the mid-1990s.